Use of early phenotypic in vivo markers to assess human relevance of an unusual rodent non-genotoxic carcinogen in vitro. (15th March 2017) - Boess, Franziska; Lenz, Barbara; Funk, Juergen; Niederhauser, Urs; Bassett, Simon; Zhang, Jitao David; Singer, Thomas; Roth, Adrian B.
Highlights: RG3487 induced foci of altered hepatocytes and subsequent liver tumors in rats. Early phenotypic markers preceding foci appearance in rats were identified. These early foci markers could be recapitulated in cellular rat liver models. A species comparison using rat, mouse and dog liver cell models qualified the approach. In vitro human data support non-human-relevance for RG3487 induced foci formation. Abstract: Foci of altered hepatocytes (FAH) are considered putative, pre-neoplastic lesions that can occur spontaneously in aging rodents, but can also be induced by chemicals or drugs. Progression of FAH to hepatocellular neoplasms has been reported repeatedly but increases in foci in rodents do not necessarily lead to tumors in carcinogenicity studies and the relevance for humans often remains unclear. Here we present the case of RG3487, a molecule which induced FAH and, later on, tumors in rats. Because the molecule was negative in genotoxicity assays it was classified as a non-genotoxic carcinogen. In order to assess the potential for liver tumor formation in humans, we analyzed treatment-induced changes in vivo to establish a possible mode of action (MoA). In vivo and in vitro gene expression analysis revealed that nuclear receptor signaling was unlikely to be the relevant MoA and no other known mechanism could be established. We therefore took an approach comparing phenotypic markers, including mRNA changes, proliferation and glycogen accumulation, in vitro using cells of different species to assess the human relevance of this finding. Since the alterations observed in rats were not seen in the liver of mice or dogs in vivo, we could validate the relevance of the cell models chosen by use of hepatocytes from these species in vitro . This ultimately allowed for a cross-species comparison, which suggested that the formation of FAH and liver tumors was rat specific and unlikely to translate to human. Our work showed that phenotypic species comparison in vitro is a useful approach for assessment of the human relevance of pre-clinical findings where no known mechanism can be established.